A Relation Between Efl Students’ Needs And Teachers’ Teaching Strategies To Encourage Students’ Involvement - sola gratia wiyana; Januarius Mujiyanto; Henrikus Joko Yulianto (Universitas Negeri Semarang, 2022)
Online English teaching and learning during the pandemic is challenging for teachers and students. One of the problems encountered by teachers is maintaining students’ involvement in class discussions. To maintain students’ involvement, it is important to implement strategies that meet students’ needs. This study aims at describing students’ objective and subjective needs in learning English. This study was descriptive qualitative in nature. It was conducted at SD Daniel Creative School, Semarang. 184 students and 6 English teachers were involved in this study. This study used a questionnaire, classroom observation sheet, and interview as the instruments. The result revealed that for objective needs, many students still needed help in mastering some areas, such as listening, speaking, reading, writing, vocabulary, and grammar. For subjective needs, many students had low self-confidence and self-esteem in learning English. In addition, the students also mentioned their expectations of teachers’ teaching strategies. The observation showed that the strategies implemented by the teachers were effective to fulfill students’ needs and to encourage their involvement in class discussions. Unfortunately, the teachers did not implement all the strategies consistently to fulfill students’ needs. As the result, students’ involvement was still low. Thus, this study implies a suggestion for English teachers of the school and English teachers, in general, to consistently implement teaching strategies that meet students’ needs to encourage students’ involvement.